1989
DOI: 10.1111/j.1475-1313.1989.tb00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual conversion reaction in children

Abstract: Visual conversion reaction (VCR) is a psychosomatic illness that will occasionally be seen by optometrists and ophthalmologists. This paper discusses some of the possible aetiologies and manifestations of the condition. Investigation and management of children with suspected VCR is discussed. Four case histories are presented in which signs of VCR included amblyopia, reduced accommodation and a deterioration in handwriting. The visual field defects presented include a static quantitative anomaly. Such a defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Many of these patients initially present to their primary care physician before seeing an ophthalmologist, so there is significant value in promoting more awareness about this disease. NOVL occurs most frequently in girls aged 8-13 [3,4]. The most common clinical presentation is reduction in visual acuity with symmetric, bilateral eye involvement [5].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these patients initially present to their primary care physician before seeing an ophthalmologist, so there is significant value in promoting more awareness about this disease. NOVL occurs most frequently in girls aged 8-13 [3,4]. The most common clinical presentation is reduction in visual acuity with symmetric, bilateral eye involvement [5].…”
Section: Discussionmentioning
confidence: 99%
“…Eames' 1947 study revealed that 9 % of a sample of 193 unselected school children had the tubular field defects characteristic of VCR. Children most commonly present at the age of 9-11 years, with some studies showing a second peak at puberty (Barnard, 1989); girls are more commonly affected than boys. Vision is usually blurred but rarely absent in one or both eyes, and there is sometimes associated diplopia or headaches.…”
Section: Introductionmentioning
confidence: 99%